2009
DOI: 10.1108/03074800910928559
|View full text |Cite
|
Sign up to set email alerts
|

The shifting landscape of e‐books

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 3 publications
3
18
0
2
Order By: Relevance
“…A review of the monthly usage statistics for Knovel and CHEMnetBASE revealed spikes in usage in the first month of each semester, when over 2,000 freshmen chemistry students are introduced to these resources. As Aline Soules points out, librarians are key brokers for students and faculty in the use of e-books (Soules 2009). Since a library assignment was added as a freshmen chemistry laboratory activity, use of Knovel and CHEMnetBASE has increased, not only because of use by freshmen but because over 180 teaching assistants as well as the faculty teaching the freshmen chemistry classes must also be familiar with the resources the students use.…”
Section: Discussionmentioning
confidence: 98%
“…A review of the monthly usage statistics for Knovel and CHEMnetBASE revealed spikes in usage in the first month of each semester, when over 2,000 freshmen chemistry students are introduced to these resources. As Aline Soules points out, librarians are key brokers for students and faculty in the use of e-books (Soules 2009). Since a library assignment was added as a freshmen chemistry laboratory activity, use of Knovel and CHEMnetBASE has increased, not only because of use by freshmen but because over 180 teaching assistants as well as the faculty teaching the freshmen chemistry classes must also be familiar with the resources the students use.…”
Section: Discussionmentioning
confidence: 98%
“…Both the nature of e-books and the information-seeking behaviour of users are changing (Soules 2009, Nicholas 2008a, and it is likely that new business models will emerge as a result. Continuing analysis of usage data at both local and national level will be needed if we are to understand how our e-book collections are being used, and ensure both that we are acquiring the e-books our users need, and that our choice of business model represents the best possible value for money.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Almost 6,500 students at both the graduate and undergraduate level responded, of whom 48.5% reported never using e-books, with 57% of those respondents explaining that they could not locate them. 38 Another accessibility issue is that patrons might not know these e-books exist in the first place. Ebrary found that 33.5% of students did not know whether their library had e-books, although 90% of librarians surveyed said they were available.…”
Section: E-books and Next-generation Catalogsmentioning
confidence: 99%